(3fXGe eYdheGJ dNOeI eJNPj GdbQGQGJs - (3GMeO UdGM(B, (3YWjIs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2007)
(3JfGhd gPG GdcJGH WHjYI heLGdGJg hGdCSS GdfXQjI ddeMGSHI GdeGdjI ceG YQVJ GdeYGOdI GdeMGSHjI heYdheGJ GdbhGFe GdeGdjI MjK HHUQI aUhdg cGdJGdj ebOeI aj fXGe GdeMGSHI GdeGdjI , GdbhGFe GdeGdjI GdCSGSjI , GdOhQI GdeMGSHjI , GdOhQI GdeMGSHjI (B: (3GdJShjGJ GdLQOjI , GdeMGSHI Ydi GdCUhd GdeJOGhdI , GdeMGSHI Ydi GdGUhd GdKGHJI , GdCReGJ hMbhb GdedcjIs
(3HjHdjhZQGajG U(B.496s
Keywords: (3GJNGP bQGQs; (3GdeMGSHI GdJMdjdjIs; (3eMGSHI eGdjIs; (3fXGe eYdheGJs